Establishment technique of Shorea Leprosula, Shorea Parvifolia and Neobalanocarpus Heimii in an acacia mangium plantations - Nagai, H. (Forestry Department Peninsular Malaysia, 2016)
In Peninsular Malaysia, Acacia mangium plantations cover about 56, 000 ha, which were formerly degraded logged-over forests. The establishment of A. mangium plantations was aimed to produce general utility timber for the wood based industries in the 1990s. However, the low quality of A. mangium timber has limited its uses and its suitability as raw material for the sawntimber and plywood industries. The low price of A. mangium logs at ex-decking site has downgraded the species as the main lantation species. Thus, this project was embarked to produce high value timbers from the existing A. mangium plantations. The project site is located at Block B, Chikus Forest Reserve, and covers about 200 ha of Acacia mangium plantation. The experimental plots cover about 42 ha comprising 15 combined treatments of three species and five types of planting line at two planting directions. Three high quality dipterocarps, namely Shorea parvifolia, S. leprosula and Neobalanocarpus heimii, were line-planted in the A. mangium removed alternately-Type A), 9.0-11.1 m (two rpws of A. mangium removed alternately- Type B), 15-18.5 m (four rows of A.mangium removed alternately-Type C), 27-33.3 m (eight rows of A. mangium removed alternately-Type D), and 51-62.9 m (16 rows of A. mangium removed alternately-Type E) were adopted for the planting trial of the three dipterocarps. Neobalanocarpus heimii had significantly the smallest mean top height and dbh amongst the three dipetrocarps showed survival of 70-80% in planting line Type-A at 8 years after planting. The findings of the experiment show that all the three dipterocarps can be grown as forest plantation species underplanting the A. mangium plantations. The paper also discusses the management model of the diterocarp plantations.